Faktor yang Mempengaruhi Keputusan Pembelian Pakaian Bekas di Pasar Aurduri Kota Jambi - Sherliny Widya; Habriyanto Habriyanto; Marissa Putriana (Master Manajemen, 2024)
The secondhand clothing market has become a popular alternative choice among consumers, especially in big cities like Jambi. This study aims to explore the factors that influence purchasing decisions of secondhand clothing in Aurduri Market, Jambi City. With the growing interest in second-hand clothing, it is important to understand the variables that influence purchasing decisions to provide deeper insights for sellers and market stakeholders. This study used a quantitative method with a sample of 40 respondents who were randomly selected. Data was collected through a questionnaire designed to evaluate the influence of price, product quality, brand, and socio-cultural factors such as local trends and norms on purchasing decisions. The results showed that price was the dominant factor influencing purchasing decisions, followed by clothing quality and seller reputation. Socio-cultural factors also influence purchasing decisions, albeit with a smaller degree of influence. The findings provide valuable insights for used clothing sellers in Aurduri Market in formulating marketing strategies, as well as enriching the literature on consumer behavior in the context of the used clothing market in Indonesia.